Energy recovery via thermal gasification from waste insulation electrical cables (Wiec) - Mota-Panizio, Roberta (2020)
The recovery of noble metals from electrical wires and cables results in waste materials such as polyvinyl chloride (PVC) and polyethylene (PE), that is, waste insulation electrical cables (WIEC), which have been processed by gasification for energy recovery. This study focused on the effect of blending the ratio of WIEC on the gasification feedstock composition and the lower heating value (LHV) of produced syngas, through controlled tests and tests under different loads on the generator. The controlled gasification experiments were carried out at blending ratios between pine biomass and WIEC of 90:10, 80:20, and 70:30 and with pine biomass only (100%). For the loads gasification, the experiments were carried out at a blending ratio of 80:20. The controlled experimental results presented that the highest hydrogen content, approximated 17.7 vol.%, was observed at a blending ratio of 70:30 between pine biomass and WIEC and the highest LHV of syngas was observed at a blending ratio of 90:10, with 5.7 MJ/Nm3. For the load gasification experiments, the results showed that the highest hydrogen content was obtained with a load of 15 kW in the generator, approximately 18.48 vol.% of hydrogen content, and the highest LHV of synthesis gas was observed during the 5 kW test, with 5.22 MJ/Nm3. Overall, the new processing of waste insulation electrical cables using a downdraft gasification reactor demonstrates great promise for high quality syngas production.